2000
DOI: 10.1089/10430340050016166
|View full text |Cite
|
Sign up to set email alerts
|

Double Suicide Gene Therapy Augments the Antitumor Activity of a Replication-Competent Lytic Adenovirus through Enhanced Cytotoxicity and Radiosensitization

Abstract: Replication-competent adenoviruses may provide a highly efficient means of delivering therapeutic genes to tumors. Previously, we evaluated in vitro a replication-competent adenovirus (Ad5-CD/TKrep) containing a cytosine deaminase (CD)/herpes simplex type 1 thymidine kinase (HSV-1 TK) fusion gene that allows lytic viral therapy to be combined with double suicide gene therapy. Both the CD/5-FC and HSV-1 TK/GCV enzyme/prodrug systems enhanced the tumor cell-specific cytopathic effects of the Ad5-CD/TKrep virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…Presumably a balance is reached between augmented GCV-induced cell killing due to production of toxic GCV metabolites versus the GCV-induced reduction of cell killing due to impaired viral replication. Our data, and that of Rogulski et al, 24 would suggest that loss of lytic killing by the virus offsets any benefits due to enhanced transgene spread.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Presumably a balance is reached between augmented GCV-induced cell killing due to production of toxic GCV metabolites versus the GCV-induced reduction of cell killing due to impaired viral replication. Our data, and that of Rogulski et al, 24 would suggest that loss of lytic killing by the virus offsets any benefits due to enhanced transgene spread.…”
Section: Discussionsupporting
confidence: 73%
“…Augmented tumor killing was only seen in those animals treated with both GCV and 5-FC. In this study, the reason for this finding was not determined for certain, however, Rogulski et al 24 showed that the HSVtk/GCV system was effective in inhibiting viral replication. Presumably a balance is reached between augmented GCV-induced cell killing due to production of toxic GCV metabolites versus the GCV-induced reduction of cell killing due to impaired viral replication.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Especially concomitant stimulation of the immune system by chemokines 46 or incorporation of two suicide genes, HSV-1 TK and E. coli CD, into a replicating adenovirus 47 have shown compelling success in animal models. When additionally improving the limited in vivo transduction efficiency with the help of intercellular cargo proteins, successful gene therapy of solid tumours seems feasible.…”
Section: Mh3924a Cells Seeded In 24-well Plates Were Transduced With mentioning
confidence: 99%
“…Conditionally replicating adenoviral vectors have already been shown to enhance significantly the therapeutic impact of cancer gene therapy strategies employing suicide genes, including the CDTK fusion gene used in this study. 41,42 In addition, Lee et al 35 have described an E1b-attenuated conditionally replicating adenovirus in which CDTK gene expression is under the control of the HSP70b promoter. Infection of DU145 prostatic carcinoma and CX-1 colorectal carcinoma cells with this adenovirus resulted in greater than 1000-fold reductions in survival following treatment with drugs and mild hyperthermia in vitro.…”
Section: Discussionmentioning
confidence: 99%